Providing a liminal space: Threshold concepts for learning in palliative medicine. (2nd April 2020) - O'Callaghan, Anne; Wearn, Andy; Barrow, Mark
Abstract: Introduction : Experience in palliative medicine provides a beneficial learning opportunity for doctors-in-training. There is, however, a gap in understanding which aspects of learning are most useful, which are problematic and how learning can best be facilitated. This study addresses that gap using the 'threshold concepts' framework. Threshold concepts are critical points of learning, often unique to a discipline. The learning occurs within a transitional or 'liminal' space and has specific characteristics including being 'troublesome' and 'transformative.' Methods : A qualitative, exploratory study was carried using the threshold concept framework. Semi-structured focus group interviews were held with doctors-in-training who had undertaken a 6-month palliative medicine attachment. Data were analysed using a content analysis approach with deductive and inductive phases, in order to identify threshold concepts. Results : Five threshold concepts were identified. Two of these, 'emotional engagement' and 'communication management, ' displayed all the typical characteristics of threshold concepts. This learning was highly valued by participants, had not occurred elsewhere in training and continued to influence practice. Conclusions : Specific threshold concepts were identified for doctors undertaking a palliative medicine placement. These highlights where specific supports are required for learning and can be used to inform curriculum design.